Operational Efficiency as a Pillar of Sustainable Green Tourism Development - PUTRI, Shera Andelia; CLARISA, Putu Saskia Cindy; CAHYANI, Ni Wayan Indah; ADELIA, Efa Fitri (PT Batara Swastika Harati, 2024)
Green tourism is an approach to destination development that emphasizes the balance between economic growth, environmental conservation, and social sustainability. It ensures that tourism contributes not only to the economy but also to the preservation of natural resources and the empowerment of local communities. In its implementation, operational efficiency plays a crucial role in optimizing tourism activities, ensuring effective resource use, and minimizing environmental impacts. Efficient management of energy, water, and waste, as well as the adoption of environmentally friendly technologies, are essential in supporting sustainable operations. This article examines the role of operational efficiency in strengthening sustainable green tourism development. Using a desk study method, relevant national and international literature was reviewed to provide a comprehensive perspective. The findings indicate that efficiency improves competitiveness, promotes environmentally responsible practices, and supports good governance in tourism management. Furthermore, it enhances transparency and accountability, aligning tourism activities with the Sustainable Development Goals (SDGs). Overall, this study offers a conceptual foundation for developing policies and strategies that encourage efficient, environmentally friendly, and socially inclusive tourism management, thereby ensuring long-term sustainability of destinations.